Portrait of a flourishing freshwater fishery: Pyhäjärvi, a lake in SW-Finland - Sarvala, J.; Helminen, H.; Auvinen, H. (Boreal Environment Research Publishing Board, 2024)
Fish yields from Pyhäjärvi, a lake in southwestern Finland, (ca. 34 kg ha–1 a–1) are much higher than expected from published relationships between yield and nutrient concentrations or primary production in lakes. The basis of this fishery has been studied since 1983 in a series of ecosystem and fisheries projects. Here we review the historical development and present state of this fishery, analyse its biological and economic basis, and speculate on its future in the changing world. The main targets of the commercial fishery have been the coregonids vendace and whitefish, both introduced into the lake during this century. However, in the 1990s, the vendace stock has declined, and the less valuable perch, roach, smelt and ruffe have become dominant in the catch. This change in the fish community seems to be primarily due to climatic factors. The main reason for the high fish yields in Pyhäjärvi is the very efficient fishery: the annual harvest approaches the total production of vendace. The simple morphometry of the lake and its short food chains contribute to the productivity of the fishery. The intensive fishing itself enhances the productivity of the vendace population. Under the prevailing food-limiting conditions, exploitation focusing on juveniles leads to faster growth and higher reproduction rates, allowing high harvest rates without a population collapse. However, the recent decline of the vendace population in Pyhäjärvi shows the vulnerability of a heavily exploited fish stock under adverse environmental conditions.